Advances in library administration and organization. Vol. 28 - Nyce, James M.; Golden, Janine; Williams, Delmus Eugene (Advances in library administration and organization, 2009)
The Advances in Library Administration and Organization Series seeks to develop a body of research literature that contributes to the base of organizational theory upon which library administrators rely. Its mix of contributions to the literature of library administration and organization is intended to be both diverse and eclectic. The volume 28 provides a collection of thought-provoking articles on issues relating to problems library managers face and strategies in addressing those challenges. The topics covered in this volume include: managing change in research libraries; the agility of library consortia and its member libraries; the evaluation of reference services; developing a recruitment strategy for a diverse workforce; the evaluation of training and professional development programs; and, collective bargaining within faculty unions on college campuses. Advances is widely read by practitioners, library and information science graduate students, and those working in associated fields of information management, and remains the premier series in its area of coverage. This latest volume adds another significant contribution to the literature of library and information centre management.